The versatile interactome of chloroplast ribosomes revealed by affinity purification mass spectrometry. Issue 1 (16th December 2020) - Westrich, Lisa Désirée; Gotsmann, Vincent Leon; Herkt, Claudia; Ries, Fabian; Kazek, Tanja; Trösch, Raphael; Armbruster, Laura; Mühlenbeck, Jens Stephan; Ramundo, Silvia; Nickelsen, Jörg; Finkemeier, Iris; Wirtz, Markus; et al.
Abstract: In plant cells, chloroplast gene expression is predominantly controlled through post-transcriptional regulation. Such fine-tuning is vital for precisely orchestrating protein complex assembly as for the photosynthesis machinery and for quickly responding to environmental changes. While regulation of chloroplast protein synthesis is of central importance, little is known about the degree and nature of the regulatory network, mainly due to challenges associated with the specific isolation of transient ribosome interactors. Here, we established a ribosome affinity purification method, which enabled us to broadly uncover putative ribosome-associated proteins in chloroplasts. Endogenously tagging of a protein of the large or small subunit revealed not only interactors of the holo complex, but also preferential interactors of the two subunits. This includes known canonical regulatory proteins as well as several new proteins belonging to the categories of protein and RNA regulation, photosystem biogenesis, redox control and metabolism. The sensitivity of the here applied screen was validated for various transiently interacting proteins. We further provided evidence for the existence of a ribosome-associated N α -acetyltransferase in chloroplasts and its ability to acetylate substrate proteins at their N-terminus. The broad set of ribosome interactors underscores the potential to regulate chloroplast gene expression on the level of protein synthesis.